Breast Feeding and Mothers Employment - Habib, Huda A.; AI-Ward, Nada J. (AL-Kindy College Medical Journal, 2012)
Background: An important factor influencing duration of breastfeeding is mother’s employment status. The nutritional, immunological, psychological and economic benefits of breastfeeding are well documented. Both UNICEF and the World Health Organization recommend mothers should breastfeed exclusively for at least 6 months.Objectives: To determine how the employment and the employment variables (type of work, time of return to work and hours of work) influence the breast feeding practices.Methods: A cross- sectional study was carried out on a sample of 200 employed mothers who had their last child been completed at least tow years. Data were collected using a questionnaire form. It was carried out during the period from 1st of April to 1st of September, 2000, in Baghdad city/ AL-Risafa in 6 different places where employed mothers of young children were expected to be found.Results: The study revealed that the impact of employment status was noted on the breast feeding initiation time, breast feeding duration and complementary food initiation time. The majority of employed mothers (56.1%) who worked shorter hours breast-feed for longer durations and starts weaning after the fourth months of the infant’s age. The highest percentage of employed mothers (75.9%) with maternity leave of six months or more breast feed for a year or more and (66.1%) start weaning later than the fourth month of the infant’s life.Conclusions: The study recognizes that employed mothers who worked shorter hours and mothers with longer maternity leaves breast feed for longer durations and start weaning later than mothers who worked long hours and mothers with shorter maternity leaves. It was concluded that most work-places lack accommodations to support breast-feeding.